THE ROLE OF INTELLECTUAL CAPITAL IN ACHIEVING EMPLOYEE’S CREATIVITY AN ANALYTICAL STUDY OF THE OPINIONS OF A SAMPLE OF GOVERNMENT BANKS IN THE CITY OF DIWANIYAH - Wathiq Hamed Rasan; Latif Abdulridha Atiyah (Scholar Express Journals, 2022)
Today's organizations cannot work in isolation from the knowledge element, which is the most important source of strength that they possess to reach the levels of competitive advantage. Purpose of this research is to study the effect of the interaction of the elements of intellectual capital and how they are combined, as well as how they affect creativity, in addition to exploring the appropriate mix of elements of intellectual capital to achieve distinction. One of the important things that organizations must know on a large scale is that intellectual capital is the most important in the modern era. The aim of this research is also to address the gap by investigating the effects of Intellectual capital on creativity in the banking sector. This research was conducted using a questionnaire form for a group of Iraqi banks through the structural modeling equation. The most important findings of the current research is that the intellectual capital contributes directly and indirectly to the achievement of creativity and institutional excellence, and the intellectual capital is positively related to creativity. From the scientific implications of the research, a set of reliable elements for obtaining intellectual capital have been identified, which is the knowledge that can be implemented and provides the important role for managers in achieving the best work for the organization
Keywords: organization; implications; managers; intellectual